Fluorine silicon manganese iron type sintered flux and preparation method and application thereof

By adding Fe2O3, CaF2, SiO2, MnO and Na2O to the sintered flux, the oxygen and manganese content in the weld is controlled, and the defects such as pores and cracks during the welding process are solved, and the excellent mechanical properties of the weld and the recycling and utilization of welding slag are achieved.

CN119839500AActive Publication Date: 2025-04-18NORTHEASTERN UNIV CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510315292.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The existing sintered flux is prone to defects such as pores and cracks during welding, resulting in a decrease in the mechanical properties of the welds and the welding slag cannot be reused, resulting in waste of resources.

Method used

Fluorosilicon manganese-type sintering flux is used to control the oxygen content and manganese content in the weld by adding a specific amount of Fe2O3, CaF2, SiO2, MnO and Na2O, and improve the arc stability and weld formation properties of the weld.

Benefits of technology

The good low-temperature toughness and slag removal performance of the weld are achieved, the welding process is stable, the metal composition and structure of the weld are uniform after welding, the surface morphology is good, and there are no defects such as pores and cracks, and the recycling of welding slag is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839500A_ABST
    Figure CN119839500A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of welding flux, in particular to fluorine-silicon-manganese-iron type sintered welding flux and a preparation method and application thereof. The fluorine silicon manganese iron type sintered flux is composed of, by mass, 36%-45% of CaF2, 11%-20% of SiO2, 31%-42% of MnO, 3%-8% of Fe2O3 and 4%-7% of Na2O. The fluorine silicon manganese iron type sintered flux is adopted for welding, so that a welding seam obtained after welding has good low-temperature toughness and deslagging performance, excellent arc stability and welding seam formability are achieved, the welding process is stable, and the welding seam obtained after welding is uniform in metal component and structure, good in surface appearance and free of defects such as air holes and cracks. The invention further provides a preparation method and application of the fluorine-silicon-manganese-iron type sintered flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flux, and in particular to a fluorine-silicon-manganese-iron type sintered flux and a preparation method and application thereof. Background Art

[0002] For submerged arc welding, in addition to the welding wire, the mechanical properties and good process performance of the weld zone are mainly determined by the flux. Flux is one of the main consumables of submerged arc welding, and plays an important role in stabilizing the arc, mechanical protection, controlling weld formation, and alloy transition during the welding process. The composition of the flux determines the welding process performance and chemical metallurgical properties, which in turn affects the organization and mechanical properties of the welded joint. Fluxes mainly include bonding flux, melting flux and sintering flux. Among them, sintering flux is a high-quality, high-efficiency, energy-saving and environmentally friendly flux. Sintering flux is smokeless, arc-free and spatter-free during welding, and has the advantages of no environmental pollution, low energy consumption and full utilization of raw materials during the production and manufacturing process.

[0003] However, in the prior art, sintered flux contains a variety of oxides, which will decompose to form free oxygen and oxygen during the welding process. Oxygen and gases such as CO formed by decarburization reaction cannot be discharged in the weld in time, which will lead to the formation of pores. Free oxygen will increase the brittleness of the weld metal, thereby causing defects such as pores and cracks in the weld metal. At the same time, the brittleness increases, which reduces the mechanical properties of the weld.

[0004] In addition, since the sintered flux contains a variety of oxides, the arc has a strong stirring and heating effect on the flux slag and the weld metal pool during the welding process, which causes the transfer of alloy elements between the flux slag and the weld metal pool. The composition and structure of the slag formed after welding are somewhat different from those of the original flux. This results in a large amount of submerged arc welding sintered flux becoming a disposable consumable, and the slag formed after welding cannot be reused, which causes a waste of resources and is not conducive to environmental protection.

[0005] Therefore, it is of great significance to provide a sintering flux with excellent performance and recyclability.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The first purpose of the present invention is to provide a fluorine-silicon-manganese-iron type sintered flux, which, by adding a certain amount of Fe2O3 and synergizing with specific amounts of CaF2, SiO2, MnO and Na2O, not only makes the weld obtained after welding have good low-temperature toughness and slag removal performance, but also has excellent arc stability and weld formability, the welding process is stable, the weld metal composition and structure obtained after welding are uniform, the surface morphology is good, and there are no defects such as pores and cracks.

[0008] The second object of the present invention is to provide a method for preparing a fluorine-silicon-manganese-iron type sintered flux, by which a sintered flux with excellent performance can be obtained, and the method has the advantages of simple operation and suitability for mass production.

[0009] The third object of the present invention is to provide an application of a fluorine-silicon-manganese-iron type sintered flux in welding HSLA steel.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: The present invention first provides a fluorine-silicon-manganese-iron type sintered flux, which is composed of the following components in mass percentage: CaF2 36%-45%, SiO2 11%-20%, MnO 31%-42%, Fe2O 33%-8% and Na2O 4%-7%.

[0011] Furthermore, the low-temperature impact energy of the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux at -40°C is ≥41J.

[0012] Furthermore, the acicular ferrite content in the welded joint obtained by welding HSLA steel with fluorine-silicon-manganese-iron type sintered flux is 15%~32%.

[0013] The present invention further provides a method for preparing a fluorine-silicon-manganese-ferro type sintered flux, comprising the following steps: after uniformly mixing CaF2, SiO2, MnO and Fe2O3, adding water glass thereto and granulating to obtain mixed material particles; after drying the mixed material particles, sintering to obtain a fluorine-silicon-manganese-ferro type sintered flux.

[0014] Furthermore, the molecular formula of water glass is Na2O·nSiO2, where n is the modulus, n=2.8.

[0015] Furthermore, the water content of water glass is 45% to 55%.

[0016] Furthermore, the particle size of the mixture particles is 20 mesh to 50 mesh.

[0017] Furthermore, the sintering temperature is 700°C to 900°C.

[0018] Furthermore, the sintering holding time is 2h~4h.

[0019] The invention also provides the use of fluorine-silicon-manganese-iron type sintered flux in welding HSLA steel, and the welding method is submerged arc welding.

[0020] Furthermore, the welding line energy is 57kJ / cm~63kJ / cm.

[0021] Furthermore, the welding speed is 480 mm / min~520 mm / min.

[0022] Furthermore, during the welding process, direct current is used in the electrode forward direction, and the welding current is 840A~860A, and the welding voltage is 30V~35V.

[0023] Furthermore, during the welding process, the electrodes are reversed to use alternating current, and the welding current is 600A~650A, and the welding voltage is 34V~38V.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The fluorine-silicon-manganese-iron type sintered flux provided by the present invention, by adding a certain amount of Fe2O3 and synergizing with specific amounts of CaF2, SiO2, MnO and Na2O, not only makes the weld obtained after welding have good low-temperature toughness and slag removal performance, but also has excellent arc stability and weld formability. The welding process is stable, and the metal composition and structure of the weld obtained after welding are uniform, the surface morphology is good, and there are no defects such as pores and cracks.

[0025] (2) The fluorine-silicon-manganese-iron sintered flux provided by the present invention, by adding a certain amount of Fe2O3, on the one hand, makes the oxygen content of the weld metal more reasonable, which can ensure that the weld has excellent mechanical properties. On the other hand, it is beneficial to the oxidation of C, thereby enhancing the decarburization effect of the recycled flux, and can also achieve the Fe2O3 content in the welding slag. t Recycling of O can not only avoid waste of resources and energy, but also reduce production and processing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a macroscopic morphology of the weld obtained after welding of Example 5 provided by the present invention; Figure 2 This is a macroscopic fracture morphology of the weld obtained after welding of Example 5 provided by the present invention; Figure 3 for Figure 2 Enlarged view within the dashed box; Figure 4 A picture of the welded joint of Example 5 provided by the present invention after welding; Figure 5 A picture of the welded joint of Example 5 provided by the present invention after slag removal; Figure 6A picture of the slag shell that has fallen off in Example 5 provided by the present invention; Figure 7 This is a macroscopic morphology of the weld obtained after welding of Comparative Example 1 provided by the present invention; Figure 8 This is a macroscopic fracture morphology of the weld obtained after welding of Comparative Example 1 provided by the present invention; Fig. 9 for Figure 8 Enlarged view within the dashed box; Fig.10 This is a picture of the welded joint of Comparative Example 1 provided by the present invention after slag removal. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If the specific conditions are not indicated in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0029] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0030] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0031] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0032] In a first aspect, the present invention provides a fluorine-silicon-manganese-iron type sintered flux, which is composed of the following components in mass percentage: CaF2 36%~45%, SiO2 11%~20%, MnO 31%~42%, Fe2O 33%~8% and Na2O 4%~7%.

[0033] In the prior art, too little oxygen content in the weld will make it difficult to form fine and dispersed inclusions in the weld. This is because oxygen is one of the essential elements for the nucleation of inclusions in the weld. Too few inclusions will cause the weld to have harmful structures such as polygonal ferrite, grain boundary ferrite, and side plate ferrite. These structures are formed when heat accumulates in the weld under excessive heat input, which is not conducive to improving the strength and toughness of the welded joint. In addition, too high an oxygen content will cause defects such as pores and cracks to form inside the weld, and will greatly increase the brittleness of the weld, which can easily lead to sudden fracture of the structural parts. Therefore, it is of great significance to strictly control the oxygen content.

[0034] The fluorine-silicon-manganese-iron type sintered flux provided by the present invention contains Fe2O3, so it can provide oxygen potential during the welding process, and the oxygen content in the weld metal is more reasonable, controlled at about 500ppm, and also plays a role in decarburization, while promoting the formation of inclusions with a size of less than 2 microns, which are dispersed in the weld and pinned at the grain boundaries of austenite grains and inside the grains.

[0035] At the same time, MnO can improve the deposition efficiency of welding. MnO has good electrical conductivity and thus has certain arc stabilization performance. MnO will decompose and release O2 under the action of arc plasma and promote the oxygenation of molten droplets and molten pool. At the same time, it can promote each other with Fe2O3 and improve the reaction activity. The addition of MnO in the flux will reduce the loss of Mn element in the molten pool, or realize the alloying of Mn element of weld metal by flux through slag-molten pool reaction.

[0036] SiO2 can form a network structure in the slag after welding, which can promote the slag removal performance after welding, and at the same time play a role in reasonably controlling Si in the weld, and improve the tensile strength and hardness of the welded joint and the hardenability of the molten pool during solidification.

[0037] The main function of CaF2 is to increase the basicity of the flux, reduce the oxygen potential of the flux and the oxygen content of the weld metal, optimize the physical and chemical properties of the slag, especially the control of high-temperature viscosity and surface tension, optimize the formability of the weld, and improve the tensile strength and low-temperature toughness of the weld. In addition, CaF2 can also reduce the melting point of the sintered flux. The addition of CaF2 can reduce the melting point of the sintered flux to about 1400°C, thereby greatly optimizing the heating conditions.

[0038] Fe2O3 is the key control component for achieving flux recycling. It is used to regulate the Fe-O balance between the flux slag and the molten metal pool during welding. Adding a certain amount of Fe2O3 to the flux can, on the one hand, provide oxygen potential during welding, making the oxygen content in the weld metal more reasonable, and on the other hand, ensure that the weld has excellent mechanical properties.

[0039] During welding, the molten pool is divided into three areas, namely, the droplet area, the hot zone and the cold zone. Slag-metal reactions will occur in the droplet area and the hot zone respectively. Iron oxide will decompose at high temperature to produce oxygen, thereby increasing the oxygen partial pressure to supply oxygen to the molten pool. Another part of manganese oxide will decompose into manganese and oxygen. The present invention is based on the technology of oxide metallurgy. By reasonably controlling the manganese and oxygen contents in the weld, the addition of Mn in the weld will increase the volume fraction of acicular ferrite structure in the weld metal, and the grain size of the secondary phase transformation structure in the weld metal is also refined, thereby solving the problem of heat accumulation in the molten pool due to excessive heat input in large line energy, resulting in coarse weld structure and poor mechanical properties.

[0040] It can be seen that the sintered flux with specific components and specific ratios provided by the present invention is a sintered flux with stable welding process, high mechanical properties of weld metal, uniform weld metal composition and structure, good surface morphology, and excellent slag removal performance. It is used for welding HSLA steel with good welding effect, and the obtained weld has good low-temperature toughness and slag removal performance, and is free of defects such as pores and cracks.

[0041] In addition, by adding a certain amount of Fe2O3 to the fluorine-silicon-manganese-iron type sintered flux, the flux can be recycled, which can not only avoid the waste of resources and energy, but also reduce the production and processing costs.

[0042] In the fluorine-silicon-manganese-iron type sintered flux provided by the present invention, the mass percentage content of CaF2 can also be selected to be 37%, 38%, 39%, 41%, 42%, 43% or 44%; the mass percentage content of SiO2 can also be selected to be 12%, 13%, 14%, 15%, 16%, 17%, 18% or 19%; the mass percentage content of MnO can also be selected to be 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40% or 41%; the mass percentage content of Fe2O3 can also be selected to be 4%, 5%, 6% or 7%; the mass percentage content of Na2O can also be selected to be 5% or 6%.

[0043] The use of a specific ratio is beneficial to further improve the low-temperature toughness, slag removal performance, arc stability and weld formability of the welded joint, and is beneficial to further improve the uniformity of the weld metal composition and structure.

[0044] In some specific implementations, the low-temperature impact energy of the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux is ≥41J at -40°C.

[0045] Among them, HSLA steel refers to high-strength low-alloy structural steel, also known as "micro-alloyed steel", which is a type of steel used in marine engineering.

[0046] The welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux provided by the invention has good low-temperature toughness.

[0047] In some specific embodiments, the low-temperature impact energy of the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux at -40°C is 41J~50J, including but not limited to any one of 42J, 43J, 44J, 45J, 46J, 47J, 48J, and 49J or the range between any two of them.

[0048] In some specific embodiments, the acicular ferrite content in the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux is 15% to 32%, including but not limited to any one of 16%, 17%, 18%, 19%, 20%, 22%, 23%, 25%, 27%, 28%, 30%, and 31%, or a range between any two of them.

[0049] The fluorine-silicon-manganese-iron type sintered flux provided by the present invention can be observed under a metallographic microscope to show that the content of fine structures such as acicular ferrite in the weld metal can be as high as 32%.

[0050] In a second aspect, the present invention provides a method for preparing a fluorine-silicon-manganese-iron type sintered flux, comprising the following steps: after uniformly mixing CaF2 powder, SiO2 powder, MnO powder and Fe2O3 powder, adding water glass thereto, granulating to obtain mixed material particles. After drying the mixed material particles, sintering, and cooling to obtain the fluorine-silicon-manganese-iron type sintered flux.

[0051] Among them, water glass is an aqueous solution of sodium silicate. Water glass mainly plays the role of a binder, and the addition of water glass can introduce Na2O into the sintering flux, and Na2O can improve the welding stability during the welding process.

[0052] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided by the present invention can obtain a sintered flux with better performance, improve the low-temperature toughness and slag removal performance of the weld, as well as the uniformity and surface morphology of the weld metal, without defects such as pores and cracks.

[0053] In addition, the preparation method has the advantages of simple operation and suitability for mass production.

[0054] In some specific embodiments, the molecular formula of the water glass is Na2O·nSiO2, wherein n is the modulus, n=SiO2 / Na2O (molar ratio), the modulus shows the composition of the water glass and is an important parameter of the water glass, n=2.8.

[0055] In some specific implementations, the water content of the water glass is 45% to 55%, and can also be 48%, 50% or 52%.

[0056] In some specific embodiments, the particle size of the mixture particles is 20 mesh to 50 mesh, including but not limited to any point value of 25 mesh, 30 mesh, 35 mesh, 40 mesh, 45 mesh or a range value between any two of them.

[0057] It can be understood that, during the granulation process, particles with a particle size greater than 50 mesh are crushed, and particles with a particle size less than 20 mesh are re-granulated until the particle size of all particles is 20-50 mesh, thus obtaining mixed material particles.

[0058] In some specific embodiments, the sintering temperature is 700°C~900°C, including but not limited to any point value of 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or a range between any two of them.

[0059] In some specific embodiments, the sintering holding time is 2h~4h, including but not limited to any one of 2.5h, 3h, 3.5h or a range between any two of them.

[0060] The use of the above sintering temperature and sintering time is beneficial to further improve the low-temperature toughness and slag removal performance of the welded joint, as well as the uniformity and surface morphology of the weld metal.

[0061] In some specific embodiments, the sintering device includes a corundum crucible.

[0062] In some specific implementations, the sintering further includes a screening step, and the particle size of the fluorine-silicon-manganese-iron type sintering flux obtained after screening is 20 mesh to 50 mesh.

[0063] In some specific embodiments, the mixing time is 50 min to 60 min, including but not limited to any one of 52 min, 54 min, 56 min, and 58 min or a range between any two of them.

[0064] In some specific embodiments, the mixing is performed in a V-shaped blender, wherein the frequency of the V-shaped blender may be 0.5 Hz.

[0065] In some specific embodiments, the granulation is carried out in a XH433 PS granulator.

[0066] In some specific embodiments, the drying temperature is 250°C to 350°C, including but not limited to any point value of 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, and 340°C, or a range value between any two of them.

[0067] In some specific implementations, the drying time is 2 h to 4 h, including but not limited to any one of 2.5 h, 3 h, 3.5 h or a range between any two of them.

[0068] In some specific embodiments, the drying method includes drying, and the drying is performed in a tube furnace or an oven.

[0069] Adopting the above preparation parameters is conducive to obtaining a sintered flux with better performance.

[0070] In a third aspect, the present invention provides the use of a fluorine-silicon-manganese-iron type sintered flux in welding HSLA steel, wherein the welding method is submerged arc welding.

[0071] That is, the HSLA steel is welded by using a submerged arc welding method and a fluorine-silicon-manganese-iron type sintered flux, wherein the fluorine-silicon-manganese-iron type sintered flux is dried before welding.

[0072] The sintered flux with excellent performance provided by the present invention can meet the welding process of HSLA steel as the base material. The use of the sintered flux for welding HSLA steel is more conducive to improving the low-temperature toughness, slag removal performance, arc stability and weld formability of the weld joint, as well as the uniformity of the weld metal composition and structure.

[0073] In some specific embodiments, the welding line energy is 57 kJ / cm~63 kJ / cm, including but not limited to any point value of 58 kJ / cm, 59 kJ / cm, 60 kJ / cm, 61 kJ / cm, 62 kJ / cm or a range value between any two of them.

[0074] The specific parameters in the welding process are important means to control and improve the welding performance. The present invention adopts the above welding line energy, which is beneficial to improve the low temperature toughness and slag removal performance of the weld, and improve the uniformity and morphology of the weld.

[0075] In some specific embodiments, the welding speed is 480 mm / min~520 mm / min, including but not limited to any point value of 485 mm / min, 490 mm / min, 495 mm / min, 500 mm / min, 505 mm / min, 510 mm / min, 515 mm / min or a range value between any two of them.

[0076] The above welding speed is beneficial to further improve the low temperature toughness and slag removal performance of the weld, and improve the uniformity and morphology of the weld.

[0077] In some specific embodiments, during the welding process, direct current is used in the forward direction of the electrode, and the welding current is 840A~860A, including but not limited to any point value of 845A, 850A, 855A, 858A or a range value between any two of them; the welding voltage is 30V~35V, including but not limited to any point value of 31V, 32V, 33V, 34V, 35V or a range value between any two of them.

[0078] In some specific embodiments, during the welding process, the electrodes are reversed to use alternating current, and the welding current is 600A~650A, including but not limited to any point value of 605A, 610A, 615A, 620A, 625A, 630A, 635A, 640A, 645A or a range value between any two of them; the welding voltage is 34V~38V, including but not limited to any point value of 35V, 36V, 37V or a range value between any two of them.

[0079] The use of the above welding current and voltage is beneficial to further improve the low-temperature toughness and slag removal performance of the weld, and improve the uniformity and morphology of the weld.

[0080] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0081] Example 1 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 42%, SiO2 20%, MnO 31%, Fe2O 33% and Na2O 4%.

[0082] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided in this embodiment comprises the following steps: 483g of CaF2, 125g of SiO2, 356.5g of MnO and 34.5g of Fe2O3 are placed in a V-type mixer with a frequency of 0.5Hz and stirred evenly, and then 300g of water glass (Na2O·nSiO2, modulus n is 2.8, water content is 48%) is added thereto, and the mixture is mixed and stirred for 50min to obtain a mixed material, and the mixed material is placed in a XH433 PS type granulator for granulation to obtain mixed material particles with a particle size of 20 mesh to 50 mesh (particle size distribution is within the range of 20 mesh to 50 mesh); the mixed material particles are placed in a tubular furnace and dried at 350°C for 2h, and then the dried mixed material particles are placed in a muffle furnace and sintered at 700°C for 2h to obtain a fluorine-silicon-manganese-iron type sintered flux.

[0083] The fluorine-silicon-manganese-iron type sintered flux prepared in Example 1 was placed in a drying oven at a temperature of 300°C for 2 hours, and then the dried sintered flux was used to weld HSLA steel using a submerged arc welding method. The welding parameters were as follows: welding line energy was 60 kJ / cm, welding speed was 500 mm / min; direct current was used for the electrode forward direction, welding current was 850 A, and welding voltage was 32 V; alternating current was used for the electrode reverse direction, welding current was 620 A, and welding voltage was 36 V.

[0084] Example 2 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 41%, SiO2 18%, MnO 33%, Fe2O 34% and Na2O 4%.

[0085] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided in this embodiment comprises the following steps: 471.5g of CaF2, 102g of SiO2, 379.5g of MnO and 46g of Fe2O3 are placed in a V-type mixer with a frequency of 0.5Hz and stirred evenly, and then 300g of water glass (Na2O·nSiO2, modulus n is 2.8, water content is 48%) is added thereto, and the mixture is mixed and stirred for 50min to obtain a mixed material, and the mixed material is placed in a XH433 PS granulator for granulation to obtain mixed material particles with a particle size of 20-50 mesh; the mixed material particles are placed in a tubular furnace and dried at 350°C for 2h, and then the dried mixed material particles are placed in a muffle furnace and sintered at 700°C for 2h to obtain a fluorine-silicon-manganese-iron type sintered flux.

[0086] The fluorine-silicon-manganese-iron type sintered flux prepared in Example 2 was placed in a drying oven at a temperature of 350°C for 2 hours, and then the dried sintered flux was used to weld HSLA steel using a submerged arc welding method. The welding parameters were as follows: welding line energy was 57 kJ / cm, welding speed was 480 mm / min; direct current was used for the electrode forward direction, welding current was 840 A, and welding voltage was 30 V; alternating current was used for the electrode reverse direction, welding current was 600 A, and welding voltage was 34 V.

[0087] Example 3 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 40%, SiO2 16%, MnO 35%, Fe2O 34% and Na2O 5%.

[0088] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided in this embodiment comprises the following steps: 460g of CaF2, 70g of SiO2, 402.5g of MnO and 46g of Fe2O3 are placed in a V-type mixer with a frequency of 0.5Hz and stirred evenly, and then 300g of water glass (Na2O·nSiO2, modulus n is 2.8, water content is 52%) is added thereto, mixed and stirred for 50min to obtain a mixed material, and the mixed material is placed in a XH433 PS granulator for granulation to obtain mixed material particles with a particle size of 20-50 mesh; the mixed material particles are placed in a tubular furnace and dried at 350°C for 2h, and then the dried mixed material particles are placed in a muffle furnace and sintered at 700°C for 2h to obtain a fluorine-silicon-manganese-iron type sintered flux.

[0089] The fluorine-silicon-manganese-iron type sintered flux prepared in Example 3 was placed in a drying oven at a temperature of 330°C for 2.5 hours, and then the dried sintered flux was used to weld HSLA steel using a submerged arc welding method. The welding parameters were as follows: welding line energy was 63 kJ / cm, welding speed was 520 mm / min; direct current was used for the electrode forward direction, welding current was 860 A, and welding voltage was 35 V; alternating current was used for the electrode reverse direction, welding current was 650 A, and welding voltage was 38 V.

[0090] Example 4 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 39%, SiO2 14%, MnO 37%, Fe2O 34% and Na2O 6%.

[0091] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided in this embodiment comprises the following steps: 448.5g of CaF2, 47g of SiO2, 425.5g of MnO and 46g of Fe2O3 are placed in a V-type mixer with a frequency of 0.5Hz and stirred evenly, and then 300g of water glass (Na2O·nSiO2, modulus n is 2.8, water content is .52%) is added thereto, and the mixture is mixed and stirred for 50min to obtain a mixed material, and the mixed material is placed in a XH433 PS granulator for granulation to obtain mixed material particles with a particle size of 20-50 mesh; the mixed material particles are placed in a tubular furnace and dried at 350°C for 2h, and then the dried mixed material particles are placed in a muffle furnace and sintered at 700°C for 2h to obtain a fluorine-silicon-manganese-iron type sintered flux.

[0092] The fluorine-silicon-manganese-iron type sintered flux prepared in Example 4 was placed in a drying oven at a temperature of 290°C and dried for 3.5 hours, and then the dried sintered flux was used to weld HSLA steel using a submerged arc welding method. The welding parameters were as follows: welding line energy was 58 kJ / cm, welding speed was 490 mm / min; direct current was used for the electrode forward direction, welding current was 850 A, and welding voltage was 33 V; alternating current was used for the electrode reverse direction, welding current was 630 A, and welding voltage was 35 V.

[0093] Example 5 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 38%, SiO2 12%, MnO 40%, Fe2O 35% and Na2O 5%.

[0094] The preparation method of the fluorine-silicon-manganese-iron type sintered flux provided in this embodiment comprises the following steps: 437g of CaF2, 28g of SiO2, 460g of MnO and 57.5g of Fe2O3 are placed in a V-type mixer with a frequency of 0.5Hz and stirred evenly, and then 300g of water glass (Na2O·nSiO2, modulus n is 2.8, water content is 50%) is added thereto, mixed and stirred for 50min to obtain a mixed material, and the mixed material is placed in a XH433 PS type granulator for granulation to obtain mixed material particles with a particle size of 20-50 mesh; the mixed material particles are placed in a tubular furnace and dried at 350°C for 2h, and then the dried mixed material particles are placed in a muffle furnace and sintered at 700°C for 2h to obtain a fluorine-silicon-manganese-iron type sintered flux.

[0095] The fluorine-silicon-manganese-iron type sintered flux prepared in Example 5 was placed in a drying oven at a temperature of 350°C and dried for 2 hours, and then the dried sintered flux was used to weld HSLA steel using a submerged arc welding method. The welding parameters were as follows: welding line energy was 60 kJ / cm, welding speed was 500 mm / min; direct current was used for the electrode forward direction, welding current was 850 A, and welding voltage was 32 V; alternating current was used for the electrode reverse direction, welding current was 625 A, and welding voltage was 36 V.

[0096] The macroscopic morphology of the weld after welding in this embodiment is as follows Figure 1 As shown, from Figure 1 It can be seen that after welding, the weld has uniform composition, good surface morphology and good slag removal properties.

[0097] The macroscopic fracture morphology of the weld after welding in this embodiment is as follows: Figure 2 As shown, Figure 3 for Figure 2 The enlarged image in the dotted frame is the microscopic fracture morphology. Figure 2 and Figure 3 It can be seen that the impact fracture morphology of the weld is a ductile fracture, and the dimple diameter is small and the density is large, which can absorb a large amount of energy released during fracture, and can effectively avoid sudden fracture during use and avoid the occurrence of various accidents.

[0098] It can be seen that the present invention has excellent arc stability and weld formability by adding a certain amount of Fe2O3 and synergizing with CaF2, SiO2, MnO and Na2O, and the welding process is stable. The weld metal composition and structure obtained after welding are uniform, the surface morphology is good, and there are no defects such as pores and cracks.

[0099] Example 6 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 37%, SiO2 13%, MnO 40%, Fe2O 36% and Na2O 4%.

[0100] The preparation method of the sintered flux provided in this embodiment is basically the same as that in Embodiment 5, except that the mass of the raw materials is replaced with 425.5 g CaF2, 39.5 g SiO2, 460 g MnO and 69 g Fe2O3 (the mass of water glass remains unchanged), and the sintering temperature in this embodiment is 840°C.

[0101] The fluorine-silicon-manganese-iron type sintered flux prepared in this example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0102] Example 7 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 36%, SiO2 11%, MnO 41%, Fe2O 37% and Na2O 5%.

[0103] The preparation method of the sintered flux provided in this embodiment is basically the same as that in Embodiment 5, except that the mass of the raw materials is replaced with 414g CaF2, 16.5g SiO2, 471.5g MnO and 80.5g Fe2O3 (the mass of water glass remains unchanged), and the sintering temperature in this embodiment is 880°C.

[0104] The fluorine-silicon-manganese-iron type sintered flux prepared in this example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0105] Example 8 The fluorine-silicon-manganese-iron type sintered flux provided in this embodiment is composed of the following components in percentage by mass: CaF2 36%, SiO2 11%, MnO 38%, Fe2O 38% and Na2O 7%.

[0106] The preparation method of the sintered flux provided in this embodiment is basically the same as that in Embodiment 5, except that the mass of the raw materials is replaced with 414g CaF2, 16.5g SiO2, 437g MnO and 92g Fe2O3 (the mass of water glass remains unchanged), and the sintering temperature in this embodiment is 900°C.

[0107] The fluorine-silicon-manganese-iron type sintered flux prepared in this example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0108] Comparative Example 1 The sintered flux provided in this comparative example consists of the following components in percentage by mass: CaF2 38%, SiO2 32%, MnO 20%, Fe2O 35% and Na2O 5%.

[0109] The preparation method of the sintered flux provided in this comparative example is basically the same as that of Example 5, except that the mass of the raw materials is replaced with 437 g CaF2, 258 g SiO2, 230 g MnO and 57.5 g Fe2O3 (the mass of the water glass remains unchanged).

[0110] The sintered flux prepared in this comparative example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0111] Comparative Example 2 The sintered flux provided in this comparative example consists of the following components in percentage by mass: CaF2 38%, SiO2 22%, MnO 30%, Fe2O 35% and Na2O 5%.

[0112] The preparation method of the sintered flux provided in this comparative example is basically the same as that of Example 5, except that the mass of the raw materials is replaced with 437 g CaF2, 143 g SiO2, 345 g MnO and 57.5 g Fe2O3 (the mass of the water glass remains unchanged).

[0113] The sintered flux prepared in this comparative example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0114] Comparative Example 3 The sintered flux provided in this comparative example consists of the following components in percentage by mass: CaF2 54%, SiO2 11%, MnO 20%, Fe2O 38% and Na2O 7%.

[0115] The preparation method of the sintered flux provided in this comparative example is basically the same as that of Example 5, except that the mass of the raw materials is replaced with 621 g CaF2, 16.5 g SiO2, 230 g MnO and 92 g Fe2O3 (the mass of the water glass remains unchanged).

[0116] The sintered flux prepared in this comparative example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0117] Comparative Example 4 The sintered flux provided in this comparative example consists of the following components in percentage by mass: CaF2 43%, SiO2 12%, MnO 40% and Na2O 5%.

[0118] The preparation method of the sintered flux provided in this comparative example is substantially the same as that of Example 5, except that Fe2O3 is not added and the mass of CaF2 is replaced with 494.5 g.

[0119] The sintered flux prepared in this comparative example is used to weld HSLA steel, and the welding method is exactly the same as that in Example 5.

[0120] Experimental example The welded joints obtained by welding in each embodiment and each comparative example were tested for acicular ferrite content, inclusion number density, proportion of inclusions with a diameter <2 μm (number proportion) and low-temperature impact energy (-40°C). The results are shown in Table 1 below.

[0121] The content of acicular ferrite was measured by the intercept method under an OLYMPUS GX51 metallographic microscope with the weld joint sample magnified 200 times.

[0122] The test method for the number density of inclusions is as follows: a TESCAN MIRA3 field emission scanning electron microscope is used to take samples of the welded joint and photograph them at 5000 times magnification for statistical analysis.

[0123] The test of low temperature impact energy (-40℃) refers to GB / T 2650-2008, and the instrument used is SANS-ZBC2452-C impact testing machine.

[0124] Table 1 Performance test results of each group of welding joints

[0125] It can be seen from Table 1 that the low-temperature toughness of the welded joints obtained in each embodiment is good, especially in Example 5, the low-temperature impact energy (-40°C) is 50J, which is much greater than the national standard 34J, and the acicular ferrite content is 32%. However, the low-temperature toughness of the welded joints obtained in each comparative example is poor, which is less than the national standard 34J, and the acicular ferrite content is ≤13%.

[0126] Further, pictures of the welded joints of Example 5 and Comparative Example 1 after welding and pictures after slag removal were taken, and the results are as follows: Figure 4~Figure 10 As shown. Among them, Figure 4 This is a picture of the welded joint of Example 5 after welding. Figure 5 This is a picture of the welded joint of Example 5 after slag removal. Figure 6 This is a picture of the slag shell that fell off in Example 5. Figure 7 This is the macroscopic morphology of the weld of Comparative Example 1 after welding. Figure 8 This is the macroscopic fracture morphology of the weld after welding in Comparative Example 1. Fig. 9 for Figure 8 The enlarged image within the dotted frame is the microscopic fracture morphology. Fig.10 This is a picture of the welded joint of Comparative Example 1 after slag removal.

[0127] from Figure 4 and Figure 5 It can be seen that the weld of Example 5 has no defects and good slag removal performance. Figure 6 It can be seen that the slag shell that falls off in Example 5 has a smooth surface and has an excellent protection effect on the weld, which further illustrates its good slag removal performance.

[0128] from Figure 8 and Fig. 9 It can be seen that the impact fracture morphology of the weld of Comparative Example 1 is brittle fracture, with a large number of river-shaped cleavage planes, and poor impact performance. Fig.10 It can be seen that part of the slag shell is adhered to the surface of the weld joint of Comparative Example 1, and the slag cannot be completely removed, that is, the slag removal performance of Comparative Example 1 is poor.

[0129] It can be seen that the present invention, by adding a certain amount of Fe2O3 and synergizing with CaF2, SiO2 and MnO, and by controlling the manganese and oxygen contents in the weld, makes the weld have good low-temperature toughness (greater than the national standard 34J) and slag removal performance when the acicular ferrite content is low.

[0130] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A fluorine-silicon-manganese-iron type sintered flux, characterized in that: The following components are calculated by weight percentage: Composition: CaF2 36%~45%, SiO2 11%~20%, MnO 31%~42%, Fe2O3 3%~8% and Na2O 4%~7%.

2. The fluorine-silicon-manganese-iron type sintered flux according to claim 1, characterized in that: The low-temperature impact energy of the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux at -40°C is ≥41J.

3. The fluorine-silicon-manganese-iron type sintered flux according to claim 1, characterized in that: The acicular ferrite content in the welded joint obtained by welding HSLA steel with the fluorine-silicon-manganese-iron type sintered flux is 15%-32%.

4. A method for preparing the fluorine-silicon-manganese-iron type sintered flux according to any one of claims 1 to 3, characterized in that: The steps include: After CaF2, SiO2, MnO and Fe2O3 are uniformly mixed, water glass is added thereto and granulated to obtain mixed material particles; The mixed material particles are dried and then sintered to obtain the fluorine-silicon-manganese-iron type sintered flux.

5. The method for preparing the fluorine-silicon-manganese-iron type sintered flux according to claim 4, characterized in that: The molecular formula of the water glass is Na2O·nSiO2, wherein n is the modulus, n=2.8; and the water content of the water glass is 45%-55%.

6. The method for preparing the fluorine-silicon-manganese-iron type sintered flux according to claim 4, characterized in that: The particle size of the mixed material particles is 20 mesh to 50 mesh.

7. The method for preparing the fluorine-silicon-manganese-iron type sintered flux according to claim 4, characterized in that: The sintering temperature is 700° C. to 900° C., and the sintering holding time is 2 h to 4 h.

8. Use of the fluorine-silicon-manganese-iron type sintered flux according to any one of claims 1 to 3 in welding HSLA steel, characterized in that: The welding method is submerged arc welding.

9. The use of the fluorine-silicon-manganese-iron type sintered flux in welding HSLA steel according to claim 8, characterized in that: The welding line energy is 57kJ / cm~63kJ / cm, and the welding speed is 480mm / min~520mm / min.

10. The use of the fluorine-silicon-manganese-iron type sintered flux in welding HSLA steel according to claim 8, characterized in that: During the welding process, the electrode adopts direct current in the forward direction, and the welding current is 840A~860A, and the welding voltage is 30V~35V; During the welding process, the electrodes are reversed to use alternating current, and the welding current is 600A~650A, and the welding voltage is 34V~38V.

Citation Information

Patent Citations

  • Sintering welding flux with high alkalinity

    CN1040160A

  • Submerged-arc welding flux for 800MPa-grade high-strength steel for large-size hydropower facility and production method of submerged-arc welding flux

    CN107745203A

  • Sintered flux for welding HSLA steel and preparation method thereof

    CN113695789A

  • Zirconium-manganese-silicon-titanium type environment-friendly sintered flux and preparation method and application thereof

    CN115502611A

  • Sintered flux for duplex pipe submerged arc girth welding and preparation method of sintered flux

    CN116275699A